Training On Reading Classical Islamic Texts for Students of MAS Tahfidz Rokan Hulu to Improve Qirā’ah Skills - Anwar Sidik; Rina Ristiyani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study is part of a community service program to enhance students’ ability to read classical Islamic texts (maharah qirā’ah) at MAS Tahfidz Rokan Hulu. Kitab kuning, as a core of Islamic scholarly tradition, demands strong Arabic grammar skills, especially in nahwu and sharaf, due to its unvowelled format. Despite their diniyah background, many students still struggle to comprehend these texts independently. Using a descriptive-qualitative approach, this program implemented practical training strategies, including basic sentence structure review, i’rab reinforcement, vocabulary enrichment, and guided reading via halaqah and musyāwarah methods. Data from observation and interviews revealed improved understanding of Arabic grammar and greater reading fluency. The contextual, hands-on approach helped boost student confidence and engagement with classical texts. Moreover, the collaborative halaqah setting fostered active, enjoyable learning. These results highlight the value of practical strategies in kitab kuning instruction, especially for students with foundational Arabic knowledge. Strengthening maharah qirā’ah not only deepens access to turats literature but also promotes critical and religious thinking. This model is recommended for adoption in other Islamic schools or pesantren to preserve and strengthen classical Islamic scholarship. Penelitian ini merupakan bagian dari program pengabdian masyarakat yang bertujuan untuk meningkatkan kemampuan membaca teks klasik Islam (maharah qirā’ah) bagi siswa MAS Tahfidz Rokan Hulu. Kitab kuning, sebagai inti dari tradisi keilmuan Islam, menuntut penguasaan tata bahasa Arab yang kuat, khususnya dalam aspek nahwu dan sharaf, karena tidak berharakat. Meskipun para siswa memiliki latar belakang pendidikan diniyah, banyak di antara mereka yang masih kesulitan memahami teks secara mandiri. Dengan pendekatan deskriptif-kualitatif, program ini menerapkan strategi pelatihan praktis, termasuk pengenalan struktur kalimat dasar, penguatan konsep i’rab, perluasan kosakata klasik, serta latihan membaca melalui metode halaqah dan musyāwarah. Data dari observasi dan wawancara menunjukkan peningkatan pemahaman terhadap tata bahasa Arab dan kelancaran membaca teks. Pendekatan yang kontekstual dan aplikatif ini berhasil meningkatkan kepercayaan diri dan ketertarikan siswa terhadap teks-teks klasik. Selain itu, suasana kolaboratif dalam halaqah mendorong partisipasi aktif dan menyenangkan. Hasil ini menegaskan pentingnya strategi praktis dalam pembelajaran kitab kuning, terutama bagi siswa yang telah memiliki dasar bahasa Arab. Penguatan maharah qirā’ah tidak hanya memperdalam akses terhadap literatur turats, tetapi juga mendorong pemikiran kritis dan religius. Model pelatihan ini direkomendasikan untuk diterapkan di lembaga pendidikan Islam lainnya dalam rangka melestarikan tradisi keilmuan Islam klasik.